Students’ ability to understand morphological inflection in arabic texts (Analytical qualitative study at Jabal An-Nur Private Islamic High School, North Aceh) - Wahyudi, Zikri; Husaini , Husaini; Zubir, Muhammad (ARKA INSTITUTE, 2025)
Mastery of sharaf (morphology) is an important basis for understanding Arabic texts, as it enables learners to identify word patterns, recognize word roots, and accurately interpret morphological changes. This study examines students’ ability to apply morphological rules when reading Arabic texts at the Jabal An-Nur Islamic Private High School, North Aceh. Using a descriptive qualitative method, data were collected through classroom observation, semi-structured interviews, and diagnostic questionnaires given to 50 twelfth-grade students who were selected by purposive sampling based on specific criteria from a population of 543 students. The data were analyzed using descriptive qualitative analysis through the stages of data reduction, data presentation, and conclusion drawing and verification. To ensure data credibility, source and technique triangulation were used. The findings show persistent weaknesses in students’ morphological competence, especially in recognizing fi‘il mu‘tal, distinguishing verb patterns, and producing correct masdar. The questionnaire results showed that only 49% of students could correctly apply morphological rules in contextual texts. Further interview data highlighted confusion in processing empty and defective verbs. This study concludes that the lack of practical application and limited integration of morphology in reading activities contribute to these difficulties. This study recommends the implementation of contextual exercises, explicit pattern recognition training, and the use of more authentic Arabic texts to strengthen students’ morphological awareness.